Exporters and shocks: Dissecting the international elasticity puzzle - Doireann Fitzgerald; Stefanie Haller (University College Dublin, UCD School of Economics, 2014)
Aggregate exports are not very responsive to real exchange rates, though they respond strongly to trade liberalizations, a fact sometimes referred to as the International Elasticity Puzzle. We use micro data on firms and exports for Ireland to dissect the puzzle. Our identification strategy uses within-firm-year cross-market variation in real exchange rates and tariffs to identify the responses of export participation, export revenue and the product dimension of exporting to these variables. We show that (i) the weak response of export revenue of long-time market participants to real exchange rates is key to the behavior of aggregate exports, (ii) export participation also responds less to real exchange rates than to tariffs, but this alone cannot explain the puzzle; and (iii) the revenue response of long-time market participants cannot be accounted for by product entry responses. Hence any model that can successfully account for the puzzle needs to match the intensive margin responses of exporting firms.
Keywords: 330